PENGARUH KARAKTERISTIK INDIVIDU DAN KARAKTERISTIK KERJA TERHADAP ORGANIZATIONAL CITIZENSHIP BEHAVIORS DENGAN KEPUASAN KERJA SEBAGAI MEDIATOR PADA EVENT ORGANIZER DI SURABAYA - Irawan, Andy (Kajian Ilmiah Mahasiswa Manajemen, 2012)
This study aims to identify the influence of individual characteristics and job characteristics on job satisfaction and job satisfaction influences on organizational citizenship behaviors and job satisfaction in the ability to identify the mediating influence of job characteristics on organizational citizenship behaviors.Design used in this study is causal design. Exogenous variables in this study are individual characteristics and job characteristics whereas endogenous variables are job satisfaction and organizational citizenship behaviors. Sample number of 150 samples, but there are 3 of respondents had outliers so the number of samples for further research are 147 respondents. Data analysis techniques using strucutural equation model. The findings in this study suggests that individual characteristics and job characteristics proved to have a significant effect on job satisfaction. Job satisfaction is a significant effect on organizational citizenship behaviors and job satisfaction shown to mediate the effect of job characteristics on organizational citizenship behaviors.